15. ANALYSIS OF PRIMARY RENAL AND UROTHELIAL NEOPLASIA AT ROYAL NORTH SHORE HOSPITAL FROM 1998–2013. (February 2015) - Chan, Eddy; Michael, Nadav; Nkungu, Bukelwa; O'Brien, Maya; Pulbrook, Marley; Sukkar, Isabella; Watson, Nicole; Toon, Chris; Gill, Anthony J.
Abstract : The accurate pathological diagnosis of renal neoplasia both guides treatment and underlies translational research. We searched the electronic database of the department of anatomical pathology Royal North Shore Hospital for all cases of renal neoplasia and urothelial neoplasia treated by nephrectomy from 1998 to 2013. We reviewed the pathology reports to both restage according to the 7th edition 2009 staging system and to reclassify according to the ISUP Vancouver 2013 classification of renal carcinoma. The restaging and reclassification was based on review of the reports rather than slide review. We identified 415 cases and divided them in to three broad groups of renal parenchymal tumours, urothelial carcinoma and stromal tumours (angiomyolipoma, leiomyoarcoma and synovial sarcoma). Of these, 322 (77.6%) were renal parenchymal tumours, 77 (18.6%) were urothelial carcinoma and 16 (3.9%) were stromal tumours (12 angiomyolipomas, 3 leiomyosarcomas and 1 synovial sarcoma). Of the renal parenchymal tumours, 231 (71.7%) were conventional clear cell renal carcinoma, 29 (9.0%) were papillary renal cell carcinoma, 20 (6.2%) were oncocytoma, 16 (5.0%) were chromophobe renal cell carcinoma, 4 (1.2%) were sarcomatoid carcinoma, 3 (0.9%) were clear cell tubulopapillary renal cell carcinoma, 2 (0.6%) were metanephric adenoma, 2 (0.6%) were acquired cystic disease associated renal carcinoma, 1 was hereditary leiomyomatosis associated renal cell carcinoma and 1 was a mucinous and tubular spindle cell carcinoma. For 15 cases (4.7%) further subclassification into different types of renal carcinoma could not be made based on the report. The median age of patients at the time of nephrectomy were 68.0 years for renal parenchymal tumours and 75.0 years for urothelial carcinoma. Clear cell renal cell carcinoma presented with a median age of 67.0 years, papillary carcinomas 67.0 years, oncocytoma 73.0 years, and chromophobe 63.5 years.